Genotyping of the Alzheimer’s disease Genome-Wide Association Study index single nucleotide polymorphisms in the Brains for Dementia research cohort - Brookes, Keeley J.; McConnell, G.; Williams, K.; Chaudhury, Sultan R; Madhan, G.; Patel, T.; Turley, C.; Guetta-Baranes, Tamar; Francis, Paul T.; Morgan, Kevin (IOS Press, 2018)
The Brains for Dementia Research project is a recently established cohort which aims to provide brain tissue for research purposes from neuropathologically defined samples. Here we present the findings from our analysis on the 19 established GWAS index SNPs for Alzheimer’s disease, in order to demonstrate if the BDR sample also displays association to these variants. A highly significant association of the APOE ε4 allele was identified (P=3.99x10-12). Association tests for the 19 GWAS SNPs found that although no SNPs survive multiple testing, nominal significant findings were detected and concordance with the Lambert et al GWAS meta-analysis was observed.